Multicultural psychoeducational assessment - Grigorenko, Elena L.; IG Publishing (New York Springer Pub., 2009)
A very useful resource, not only for psychologists and education professionals, but universally, for all those experts interested in multicultural assessment.". --Heikki Lyytinen, PhD. Professor of Developmental Neuropsychology. University of Jyvaskyla, Finland. This volume provides a thorough and provocative examination of how different cultures measure intelligence and skill, why they use the tools they use, and how their assessment methods are changing in the globalizing world. The contributors discuss the extent to which methods of assessment are limited and culture-bound.
How universal are test development and use? / Thomas Oakland -- Equitable assessment practices in diverse contexts / Elias Mpofu, Samuel O. Ortiz -- Respecting local, cultural contexts for assessment practice in an era of globalization / Val Klenowski -- Conceptualizing developmental assessment within Africa's cultural settings / A. Bame Nsamenang -- Assessing the environment of children's learning: the developmental niche in Africa / Sara Harkness ... [et al.] -- Assessing competencies in reading and mathematics in Zambian children / Steven E. Stemler ... [et al.] -- Assessing mother tongue in the era of globalization: promise and challenge / Elena L. Grigorenko ... [et al.] -- The logic of confidence and the social economy of assessment reform in Singapore: a new institutionalist perspective / David Hogan, Phillip A. Towndrow, Kim Koh -- Instructional and assessment practices in Singapore / David Hogan, Phillip A. Towndrow, Kim Koh -- Considerations for developing and adapting language and literacy assessments in Arabic-speaking countries / Saleh Shaalan -- The behavioral characteristics of kindergarten gifted children in Saudi Arabia: construction and validation of a scale / Usama M. A. Ibrahim, Abdullah M. Aljughaiman -- Developing culture-specific assessments / Alexander G. Shmelyov, Anna S. Naumenko -- The use of foreign psychodiagnostic inventories in differing methodological contexts / Tatiana V. Kornilova, Sergey A. Kornilov -- Adapting existing abilities and competencies assessment devices to different cultures / Marcia Regina F. de Brito -- The challenge of measuring abilities and competencies in Hispanics/Latinos / Antonio E. Puente, Antonio N. Puente -- Considering language, culture, and cognitive abilities: the international translation and adaptation of the Aurora Assessment Battery / Mei T. Tan ... [et al.] -- Conclusions: assessment in an era of globalization / Peter Tymms, Robert Coe.
Electronic reproduction.
Keywords: Psychological tests; Educational tests and measurements; Cultural pluralism; Electronic books